PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM INDUSTRI PERDAGANGAN ECERAN DI BURSA EFEK INDONESIA - Toin, Dyah Rosna Yustanti; Sutrisno, Sutrisno (AMONG MAKARTI, 2015)
AbstractRetail industry is one of rapid industrial development, so the competition is also very sharp. The company is required to compete in a way boost its financial performance in order to increase its the stock price. This study aims to examine the internal factors and external factors to the stock price on the retail trade industry on the Indonesia Stock Exchange. Internal factor variables in this study consisted of earnings per share (EPS), return on equity (ROE), and return on assets (ROA), while the external factor variabels consist of interest rates and the US dollar exchange rate.The results showed that the internal factors, EPS and ROE variables significantly affect to stock price, while the variables ROI is not significantly influence stock prices. The external factors, the two variables of interest rates and the exchange rate do not have any significant effect. However, simultaneous test results showed significant effect both internal factors and external factors on stock prices Key word: earning per share, return on equity, return on investment, stock price